Implementasi ISM Code dalam Meningkatkan Keselamatan Pelayaran Kapal di Pelabuhan Tanjung Intan Cilacap - Indriyani; Robertus Igang P; Tiara Pandansari (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2021)
This study aims to determine the effect of ISM Code implementation in improving shipping safety. This research is a quantitative study by taking a sample of 75 ship crews in the Deck Department and the Engine Department who carry out loading and unloading activities at the Port of Tanjung Intan Cilacap. Data analysis using simple linear regression. This study shows that the application of the ISM Code has an effect on shipping safety.